Group work in Zoom breakout rooms to enhance English-speaking self-efficacy for active learning activities - Hartono Hartono; Elok Widiyati; Choiril Anwar (Universitas Syiah Kuala, 2023)
The study aimed at analyzing the effectiveness of assigning students to work in groups using Zoom breakout rooms to enhance their speaking self-efficacy to participate in active learning activities in an online learning context. Thirty-six students of Diploma 3 of the Accounting Program attending English for Accounting course were purposively selected as the respondents of the study. The data were collected using a three-part questionnaire distributed electronically using Google Forms. The validity and reliability of the questionnaire were measured using Pearson correlation and Cronbach Alpha. The students reported that their sources of English-speaking self-efficacy were enhanced as they had opportunities to develop both mastery and vicarious experience of English speaking, received social persuasion in the form of encouragement and motivation from one another, and experienced lower speaking anxiety. The teaching strategy enhanced the students’ English-speaking self-efficacy to participate in active learning activities to a moderate level. From being quiet and passive, they gradually transformed into active learners who could ask questions, chair discussions, answer questions, defend arguments, etc. It can be concluded that a group work in Zoom breakout rooms facilitated active learning activities as the students experienced opportunities to enhance English-speaking self-efficacy. There was a significant positive correlation between the use of group work in Zoom breakout rooms and students’ self-efficacy to participate in active learning activities. Implications and limitations of this current study are presented, and suggestions for further studies are offered.